Pengaruh Sharia Compliance, Religiositas, Kepercayaan (trust) dan Corporate Image Terhadap Keputusan Menjadi Anggota di KSPPS BMT AL-FATAA Ulujami - Lestari, Indah Ayu; Awali, Husni (Velocity: Journal of Sharia Finance and Banking, 2023)
Recently, the development of Islamic financial institutions has continued to increase. This can be seen from the increasing number of BMT which continues to increase and experiences positive growth. This indicates that many people have decided to become members and use the products and services of Islamic financial institutions. The type of research taken in this research is field research with a quantitative approach. In this study, the population taken was members of KSPPS BMT AL-FATAA totaling 6,843 people, with a sample of 100 respondents and the sampling technique used was probability sampling with simple random sampling. In this study, researchers used data collection techniques, namely questionnaires or questionnaires. The results showed that based on the t test that the sharia compliance variable had a negative and not significant effect on the decision to become a member of KSPPS BMT AL-FATAA Ulujami. The religiosity variable has a negative and insignificant effect on the decision to become a member of KSPPS BMT AL-FATAA Ulujami. The trust variable has a significant positive effect on the decision to become a member of KSPPS BMT AL-FATAA. The corporate image variable has no effect on the decision to become a member of KSPPS BMT AL-FATAA Ulujami. Based on the F test, it shows that the variables of sharia compliance, religiosity, trust and corporate image simultaneously influence the decision to become a member of KSPPS BMT AL-FATAA.